Socio-economic Comparison of Singapore, Hong Kong, and South Korea: Implications for Doing Business - OZER, Ayhan; Li, Mingyang; Diadhiou, Fatima; Fu, Likun; Vanthillo, Niels (Archives of Business Research, 2020)
Both South Korea, Hong Kong, and Singapore are part of an exclusive group called ‘The Asian Tigers’. They are high-income economies that offer some of the world’s best living conditions and most competitive business environments. In the following paper, the history, socio-economic environment and industry of Singapore, Hong Kong, and South Korea will be compared and relevant differences highlighted. Through our research, we hope to provide a comprehensive summary for everyone with an interest in conducting business in Asia.